Designing financial-incentive programs for return of service in underserved areas: seven management functions - Bärnighausen, Till; Bloom, David E. (Human resources for health, 2009)
In many countries worldwide, health worker shortages are one of the main constraints in achieving population health goals. Financial-incentive programmes for return of service, whereby participants receive payments in return for a commitment to practise for a period of time in a medically underserved area, can alleviate local and regional health worker shortages through a number of mechanisms. First, they can redirect the flow of those health workers who would have been educated without financial incentives from well-served to underserved areas. Second, they can add health workers to the pool of workers who would have been educated without financial incentives and place them in underserved areas. Third, financial-incentive programmes may improve the retention in underserved areas of those health workers who participate in a programme, but who would have worked in an underserved area without any financial incentives. Fourth, the programmes may increase the retention of all health workers in underserved areas by reducing the strength of some of the reasons why health workers leave such areas, including social isolation, lack of contact with colleagues, lack of support from medical specialists and heavy workload.
Gesehen am 10.08.2017